Les liminalités dans les représentations du cycle solaire quotidien - Danièle Dehouve (Ateliers d'Anthropologie, 2020)
The article studies the division of the daily solar cycle in Mexico, among the Aztecs of the 16th century based on ethnohistorical documents, and among the contemporary Tlapanec people based on ethnographic observations. Instead of viewing the cycle as built upon two points (sunrise and sunset) and two categories (day and night), I show that it hinges on four points (also including noon and midnight) and four categories (also including the rising sun and setting sun). Consequently, the article examines the notion of liminality, threshold or boundary and distinguishes two different types. The transitions of the first type are sunrise and sunset, here called anchoring zones; they correspond to the notion of “thick boundary” developed by Desclés to designate the existence of intermediate spaces between categories; those of the second type are the midday and midnight points, here called pivots because they constitute zones of exchange and shifting between the rising sun and setting sun.